Development Of Solid Propellant Rocket Motor - Azhar, Thaqif Naqiuddin Ahmad (Universiti Sains Malaysia, 2021)
This thesis aims to describe the process of building a solid rocket motor using a single-stage model rocket. This thesis also suggests an alternative test stand that can be built with an automated system. The finding and analysis of the rocket were obtained from the test conducted. The performance and capability of the test stand were also observed. The simulation was also run using SOLIDWORKS to test the performance of the motor casing. After through some research, more finding was discovered in maximising the performance of the rocket. In conclusion, this thesis proves that a test stand can be built to test the rocket's performance. The engineering principles also can be learned in building this rocket.